Coupling Coordination Evaluation of Water Resources and Social Economy and Obstacle Factors in the Greater Bay Area - CHEN Juan; WANG Sen; YANG Jiantao; HE Xingchang (Renmin Zhujiang)
In order to understand the coupling relationship between water resources and social economy and the main constraints in the Greater Bay Area,an evaluation index system of water resources and social economy in the Greater Bay Area is established.The coupling coordination degree model is used to evaluate the coordination states of water resources and social economy in the Greater Bay Area from 2011 to 2021,and the obstacle factors are analyzed.The results show that the coupling coordination degree of the water resources and social economy in the Greater Bay Area is between 0.43 and 0.51,which is in a low state,and the social economy system develops too fast.The degree of coupling coordination is relatively high in Zhuhai and relatively low in Foshan.The main obstacle factors are per capita water resources,per capita GDP,the proportion of tertiary industry GDP,urbanization rate,and the actual water consumption per mu of cultivated land.The research results provide a reference for the coordinated development of water resources and social economy and the planning,utilization,and management of water resources in the Greater Bay Area.